Analysis of the Influence of Different Diameters of De Laval Supersonic Nozzles on the Key Splashing Parameters of Remaining Slag - Sinelnikov, Viktor; Kalisz, Dorota; Novosád, Jan; Czarnywojtek, Piotr; Rapiejko, Cezary; Niedzielski, Piotr; Kaczorowski, Rafał; Srb, Pavel; Maia, Breno Totti; Petrů, Michal; Łoś Buczkowska, Katarzyna Ewa (Materials (Basel, Switzerland), 2024)
The paper is devoted to the analysis of a supersonic nozzle system effect in gas-cooled lances on the technological parameters of slag splashing in an oxygen converter. Simulation calculations were carried out, taking into account the parameters of nozzles used in the technological lines of converter steel plants in Ukraine and Brazil. The problems were solved in several stages. The simulation results of the first stage revealed the influence of different nozzle diameters dcr, dex and the inlet pressure before nozzle P0 on the nitrogen consumption of one nozzle Vн. Calculations also showed the influence of the critical dcr and output dex of the nozzle diameter and nitrogen flow through one nozzle Vн on the power of injected nitrogen N1 and the depth of penetration of the stream hx into the liquid slag. The second stage was dedicated to numerical simulation of the slag splashing process, including an array of results from the first stage. The thermodynamic and physical parameters were calculated using our own computer program, while 3D simulations were conducted using the ANSYS Fluent 2023 R2 program.
Keywords: optimization of process; recycling of waste material; supersonic jets; numerical modeling; thermodynamic parameters of splashing